2014
DOI: 10.1177/1533034614561358
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Cancerous Liver Cells Using Surface-Enhanced Raman Spectroscopy

Abstract: Raman spectroscopy has been widely used in biomedical research and clinical diagnostics. It possesses great potential for the analysis of biochemical processes in cell studies. In this article, the surface-enhanced Raman spectroscopy (SERS) of normal and cancerous liver cells incubated with SERS active substrates (gold nanoparticle) was measured using confocal Raman microspectroscopy technology. The chemical components of the cells were analyzed through statistical methods for the SERS spectrum. Both the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Gniadecka et al have shown different values for normal cells and basal carcinomic cells for the (1290-1360)/(1230-1290) area ratio: 0.29 (0.22-0.36) for normal cells and 1.37 (1.21-1.54) for carcinogenic cells. 75 76 The sensitivity and specificity were found to be about 90% for each case. 76 Chen et al have also proposed some parameters with values to detect cancer in the case of gastric mucosa: the 1585/853 ratio value is 0.90 AE 0.74 for cancerous samples and 0.42 AE 0.29 for normal samples with the p value being 0.03, accuracy being 73.3%, sensitivity being 67% and specificity being 80%.…”
Section: (B) Raman Ratiosmentioning
confidence: 91%
See 1 more Smart Citation
“…Gniadecka et al have shown different values for normal cells and basal carcinomic cells for the (1290-1360)/(1230-1290) area ratio: 0.29 (0.22-0.36) for normal cells and 1.37 (1.21-1.54) for carcinogenic cells. 75 76 The sensitivity and specificity were found to be about 90% for each case. 76 Chen et al have also proposed some parameters with values to detect cancer in the case of gastric mucosa: the 1585/853 ratio value is 0.90 AE 0.74 for cancerous samples and 0.42 AE 0.29 for normal samples with the p value being 0.03, accuracy being 73.3%, sensitivity being 67% and specificity being 80%.…”
Section: (B) Raman Ratiosmentioning
confidence: 91%
“…75 76 The sensitivity and specificity were found to be about 90% for each case. 76 Chen et al have also proposed some parameters with values to detect cancer in the case of gastric mucosa: the 1585/853 ratio value is 0.90 AE 0.74 for cancerous samples and 0.42 AE 0.29 for normal samples with the p value being 0.03, accuracy being 73.3%, sensitivity being 67% and specificity being 80%. 77 Huang et al have demonstrated different 656/725 ratio values for the normal and cancerous samples (0.409 AE 0.0.082 for the normal sample and 0.900 AE 0.362 for the cancerous sample), using a SERS based Raman spectroscopic method.…”
Section: (B) Raman Ratiosmentioning
confidence: 91%
“…Raman spectroscopy is such a technique, which is a kind of inelastic scattering fingerprint spectra of molecules [6]. There is a strong specificity to reflect the changes in biochemical components of living cells in aqueous solutions without any labelling and fixation [7], as such Raman spectroscopy has been employed in clinical diagnostics, toxicology tests, and tissue engineering [8,9]. Raman spectroscopy is a fast, accurate, label-free, and non-destructive analytical tool for the detection of the human cells at the single cell level [10,11].…”
Section: Sample Preparationmentioning
confidence: 99%
“…SERS can also be used to distinguish different cell types or different states of cancer. Huang et al 28 implemented the SERS method to distinguish normal liver cells from cancerous ones (hepatoma) by incubating cells with gold nanoparticles of different sizes. They showed that the relative ratios of the intensities of Raman peaks could be used to differentiate cancer cells from noncancer cells.…”
Section: Introductionmentioning
confidence: 99%